Pendampingan Pengembangan Bahan Ajar berbasis Artificial Intelligence - Ahmad, Arimuliani; Khulaifiyah; Rugaiyah (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The need for innovation in the development of teaching materials is increasingly urgent with the advancement of information and communication technologies. In an effort to improve the quality of learning, an approach based on artificial intelligence has become a highlight in modern education. This article deals with a community service project that aims to provide support in the development of AI-based teaching materials to educators. This includes training in the use of AI, the integration of technology into the learning process, and the creation of content that matches the curriculum needs. With the help of this accompaniment, educators can harness the potential of AI to improve learning effectiveness and provide a more interesting and relevant learning experience for students. The results of this accompaniment showed that the partners were satisfied with the accompanying. It's also supported ole interaction during very conducive activities. It is expected to make a positive contribution to improving the quality of education at school and college level.